INCLUSIVE EDUCATION MANAGEMENT MODEL TO IMPROVE PRINCIPAL AND TEACHER PERFORMANCE IN PRIMARY SCHOOLS - Munawir Yusuf; Sasmoko Sasmoko; Yasinta Indrianti (Universitas Sebelas Maret, 2017)
One implication of the implementation of inclusive education is the need for changes in the aspects of management in regular schools. The focus of this research is to find out whether the inclusive education management model in Elementary School (SD) developed, can assist principals and teachers in improving the effectiveness of inclusive school management in primary schools. The objectives of this study are to (1) describe the implementation of inclusive education in primary schools at present, (2) to develop an ideal model of inclusive education management in primary schools, and (3) to test the effectiveness of the inclusive education management model in primary school.This study uses the Research and Development (R & D) approach with the following stages: (1) preliminary study to find out the implementation of inclusive education implemented in SD at present, (2) development of inclusive education management model; and (3) test effectiveness Inclusive education management model developed. The research was conducted in four districts/cities, namely Surakarta, Boyolali, Sukoharjo, and Karanganyar, involving 51 SD Inclusive. Research subjects consist of Principals, Class Teachers, Special Needs Students, Non-Special Needs Students, and School Committees.The results of preliminary study concluded that (1) using performance indicators of principals and teachers, the implementation of inclusive education in primary schools is not currently in accordance with the expected criteria, (2) one of the most perceived obstacles is the unavailability of standard standards on how Good school management, (3) School Committee response, Special Needs and Non-Special Needs students on inclusive education including fairly positive categories, (4) schools have not adequately implemented the functions and aspects of school management inclusive, (5) school needs for guidance Inclusive education management including very high category.The final product of the inclusive education management model developed, requires the school to perform four management functions, namely planning, organizing, implementing and controlling, by integrating nine aspects of school management, ie institutional management, curriculum, learning, assessment, student affairs, Community participation and financing. To run the inclusive education management model effectively, an inclusive education management guide book is developed. The results of model and guidance effectiveness tests by principals and teachers show that the inclusive education management model developed has high effectiveness. Based on these results it is recommended that the inclusive education management guidebook is disseminated for use as a guide in the management of inclusive schools in primary schools in Indonesia.